AN ANALYSIS OF STUDENTS’ ANXIETY AND SELF-EFFICACY IN WRITING AT ENGLISH DEPARTMENT OF HALU OLEO UNIVERSITY - Lena, Nur; Jaya, Amir; Mursalim, Mursalim (Journal of Teaching of English, 2019)
Anxiety  is  one  of  students'  problems  in  writing.  Students  with  high anxiety have enormous impact on their writing outcomes. The purpose of this study was to find out the students anxiety in writing and their self-efficacy categories. This study employed survey design. The sample of this study was the students of the fourth semester in writing III course which consisted of 33 students.  The data  were  collected by  using close-ended  questionnaire and interview guide. The close-ended questionnaire was analyzed by using SPSS 16 version while interview  was analyzed  descriptively. The result showed that cognitive anxiety was  dominant  category of writing anxiety and  unity  was dominant category of writing self-efficacy experienced by the students.Keywords: Students Anxiety, Students Self-Efficacy, Writing Performance.